2017
DOI: 10.1155/2017/1096406
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hepatosteatosis on Response to Antiviral Treatment in Patients with Chronic Hepatitis B: A Meta-Analysis

Abstract: Background. This study is to systematically analyze the effects of hepatosteatosis on the response to antiviral treatment in patients with chronic hepatitis B (CHB) and hepatosteatosis. Methods. Systematic search was performed in PubMed, Embase, Web of Science, Elsevier, and the Chinese BioMedical literature databases for relevant studies published until February 2016. Treatment outcomes were compared between patients with CHB plus concomitant hepatosteatosis and those without hepatosteatosis. Results. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…A nested case‐control study in 267 entecavir‐treated patients with CHB found that hepatic steatosis was significantly associated with nonresponse to entecavir . Similarly, a meta‐analysis based on eight prospective cohort studies also suggested that hepatic steatosis could lower the efficacy of antiviral treatment (especially NAs) in patients with CHB . Although the impact of hepatic steatosis on antiviral therapy in these patients remains debatable, the onset or progression of NAFLD during antiviral therapy is still recommended to be monitored in case of underlying negative impacts.…”
Section: Potential Interplay Between Hepatic Steatosis and Antiviral mentioning
confidence: 99%
“…A nested case‐control study in 267 entecavir‐treated patients with CHB found that hepatic steatosis was significantly associated with nonresponse to entecavir . Similarly, a meta‐analysis based on eight prospective cohort studies also suggested that hepatic steatosis could lower the efficacy of antiviral treatment (especially NAs) in patients with CHB . Although the impact of hepatic steatosis on antiviral therapy in these patients remains debatable, the onset or progression of NAFLD during antiviral therapy is still recommended to be monitored in case of underlying negative impacts.…”
Section: Potential Interplay Between Hepatic Steatosis and Antiviral mentioning
confidence: 99%
“…Although NAFLD/HS itself is a major cause of CLD [4,5], it can also develop in patients who already have various CLDs. HS is reported to be a major factor causing ALT elevation in HBV-infected patients with a low viral load [6,7], and a meta-analysis suggested that the presence of HS may influence the efficacy of antiviral therapy, especially in nucleotide/nucleoside analogue (NA) treatment; this effect is less commonly observed in patients undergoing pegylated-interferon (PEG-IFN) treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…If a liver biopsy is not performed and antiviral treatment is only based on a transaminase abnormality, the 33.3% of patients may be treated using the wrong regimen. Our results explained that if only a transaminase abnormality is used as the indication for antiviral treatment in CHB and NAFLD coexistent patients, some chronic inflammation caused by NAFLD may be wrongly treated by antiviral therapy, resulting in poor response [1].…”
Section: Discussionmentioning
confidence: 81%
“…Hepatitis B virus (HBV) infection is one of the major causes of chronic liver disease, which ranges from chronic hepatitis to liver cirrhosis and even hepatocellular carcinoma [1,2]. It is estimated that HBV infection afflicts approximately 240 million patients with chronic hepatitis B (CHB) worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation